Sexual risk-taking and subcortical brain volume in adolescence. Issue 5 (6th April 2018) - Feldstein Ewing, Sarah W; Hudson, Karen A; Caouette, Justin; Mayer, Andrew R; Thayer, Rachel E; Ryman, Sephira G; Bryan, Angela D
Abstract : Among adolescents, brain areas involved the processing of social and emotional information were connected to their decision to use condoms when having sex. Even though many people equate sex with reward, no evidence emerged in this age group for the connection between reward-related brain areas and condom use Abstract: Background: The developmental period of adolescence marks the initiation of new socioemotional and physical behaviors, including sexual intercourse. However, little is known about neurodevelopmental influences on adolescent sexual decision-making. Purpose: We sought to determine how subcortical brain volume correlated with condom use, and whether those associations differed by gender and pubertal development. Methods: We used FreeSurfer to extract subcortical volume among N = 169 sexually experienced youth (mean age 16.07 years; 31.95% female). We conducted multiple linear regressions to examine the relationship between frequency of condom use and subcortical volume, and whether these associations would be moderated by gender and pubertal development. Results: We found that the relationship between brain volume and condom use was better accounted for by pubertal development than by gender, and moderated the association between limbic brain volume and condom use. No significant relationships were observed in reward areas (e.g., nucleus accumbens) or prefrontal cortical control areas. Conclusions: These data highlight the potential relevance of subcortical socioemotional processing structures in adolescents' sexual decision-making.